Burden of primary care‐type emergency department presentations using clinical assessment by general practitioners: A cross‐sectional study. (25th February 2019) - Whyatt, David; Tuson, Matthew; Haynes, Emma; Mountain, David; Nagree, Yusuf; Vickery, Alistair W
Abstract: Objective: To compare methods of assessment of the burden of primary care‐type ED (PCTED) presentations against clinical assessment by general practitioners (GPs) in ED. Methods: A cross‐sectional study involving clinical assessment of patients presenting to four EDs in Western Australia. The GPs assessed patients who were likely to be discharged home from ED, and considered whether they could be managed in general practice. Patient presentations were defined by the GPs as: PCTED; PCTED if additional primary care resources were available; or not PCTED. Results: GP researchers determined that 80% of patients assessed were PCTED presentations, with one‐third of these considered PCTED presentations if additional resources were available. A high proportion of identified PCTED presentations included categories excluded by previous methods. Analysis of linked data found the cohort assessed to be of lower urgency, younger, and with a shorter length of stay than the average patient being discharged from ED. After accounting for potential bias, it is suggested that 20–40% of all ED presentations could be PCTED presentations. Conclusions: Previous methods determining the burden of PCTED presentations have not been validated. Many presentations excluded by previous methods were identified as manageable in general practice by GPs clinically assessing patients in ED. Improved validation of criteria used to identify PCTED presentations will enable appropriately designed interventions to reduce such events.